2022
DOI: 10.2174/1386207324666210217144306
|View full text |Cite
|
Sign up to set email alerts
|

The Life Cycle and in silico Elucidation of Non-structural Replicating Proteins of HCV Through a Pharmacoinformatics Approach

Abstract: Background: Hepatitis C virus (HCV) is an enveloped and positive-stranded RNA virus that is a major causative agent of chronic liver diseases worldwide. HCV has become the main cause of liver transplantations and there is no effective drug for all hepatitis genotypes. Elucidation of life cycle and nonstructural proteins of HCV involved in viral replication are the attractive targets for the development of antiviral drugs. Methods: In this work, pharmacoinformatics approaches coupled with docking analyses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The ADMET properties analyses of the selected compounds were crossverified and found similar results. The toxicity analyses and the observed toxicity calculations help in the evaluation of different pollutants, metabolites and intermediates [15]. The solubility of water molecules at 25°C was also calculated for the scrutinized compounds and it was observed that all the scrutinized compounds showed water solubility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ADMET properties analyses of the selected compounds were crossverified and found similar results. The toxicity analyses and the observed toxicity calculations help in the evaluation of different pollutants, metabolites and intermediates [15]. The solubility of water molecules at 25°C was also calculated for the scrutinized compounds and it was observed that all the scrutinized compounds showed water solubility.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding this link between SP4 and schizophrenia is critical for the development of effective treatments and interventions for this complex mental illness [8]. There has been impressive progress reported in computational drug design and immuno-informatics [9][10][11][12][13][14][15][16][17][18][19][20][21][22] over the last two decades. Various problems in life sciences and biological sciences have been solved by using the different applications and approaches of computational biology [2].…”
Section: Introductionmentioning
confidence: 99%
“…Various bioinformatics techniques have been utilized to solve numerous biological problems [10]. Progressive improvements have been observed in immunoinformatics [11][12][13][14] and computational drug designing [10,[15][16][17][18][19][20][21][22][23] from last decade. Various problems of biology have been resolved through applying bioinformatics approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The achievement of immuno-informatics research and computerized drug design has significantly increased during the preceding fifteen years. The in silico, bioinformatics, and immunoinformatic techniques have been used to answer numerous biological problems [6][7][8][9][10][11][12][13][14]. The molecular docking analyses were used in the current in silico effort to identify the novel molecules against ADA.…”
Section: Introductionmentioning
confidence: 99%